General conclusions - Purriel, Juan A (Cirugía del Uruguay, 1973)
As a summary of this Round Table, we can conclude that "soft tissue sarcomas", despite their low incidence, are tumors that pose important pathologists problems that it is necessary to know to make a correct diagnosis.